2011
DOI: 10.1002/lary.21353
|View full text |Cite
|
Sign up to set email alerts
|

Interposition vein grafts in microvascular head and neck reconstruction

Abstract: Interposition vein grafts are used most often in cases involving a threatened flap, prior free flap, flap failure or radiation, and tumor recurrence. The use of interposition vein grafting in microvascular reconstruction is not associated with decreased flap survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 6 publications
(5 reference statements)
1
53
0
1
Order By: Relevance
“…In other regions of the body, including the head and neck, similar success rates have been demonstrated in large series (2). Yet other studies draw concern to the use of IVG with slightly higher rates of failure.…”
Section: Discussionmentioning
confidence: 64%
“…In other regions of the body, including the head and neck, similar success rates have been demonstrated in large series (2). Yet other studies draw concern to the use of IVG with slightly higher rates of failure.…”
Section: Discussionmentioning
confidence: 64%
“…Furr et al presented a retrospective study of 1143 patients with no significant differences in survival of flaps in cases with a vein graft compared with control. 11 However, others have reported increased failure rates that might be associated with the fact that vein grafts are used in cases where there is no available vessel for anastomosis within the reach of the pedicle. 12 This can be seen for example, in previously irradiated patients who needed a vein graft (22/28 grafts in our analysis).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative recipient sites that have been suggested when ipislateral TCA is unsuitable include: ipsilateral superficial temporal artery (STA), ipsilateral thoracoacromial branches, ipsilateral internal mammary artery, contralateral neck vessels, and even branches of a previous or simultaneous flap (Hanasono et al, ; Miller, Schusterman, Reece, & Kroll, ). While all these sources can provide a reliable arterial inflow, they often require additional incisions and sometimes long interposition venous graft to brigde the arterial gap (Biemer, ; Furr, Cannady, & Wax, ). Use of interposition vein grafts (IVG) in head and neck reconstruction remains controversial (Kruse, Luebbers, Gratz, & Obwegeser, ).…”
Section: Discussionmentioning
confidence: 99%
“…Use of interposition vein grafts (IVG) in head and neck reconstruction remains controversial (Kruse, Luebbers, Gratz, & Obwegeser, ). Furr et al () reported 95% free flap survival rate with the use of IVGs in head and neck reconstruction. On the other hand, other authors have reported up to 24% free flap loss when IVGs are used, especially in salvage cases (Nelson et al, ).…”
Section: Discussionmentioning
confidence: 99%